2019
DOI: 10.1108/ijhg-07-2018-0030
|View full text |Cite
|
Sign up to set email alerts
|

Designing a pragmatic model for strategic purchasing of health services in health insurance companies

Abstract: Purpose The purpose of this paper is to identify the most important factors for strategic purchasing of health services in the health sector by the Iran Health Insurance Company and to provide an applicable model for other similar organizations in developing countries. Design/methodology/approach The present qualitative study was conducted in 2017 to identify the factors affecting the implementation of strategic purchasing of health services in the health sector by the Iran Health Insurance Company and to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The potential for a fair contract between the buyer and the service provider has been emphasized in many studies as a strategic purchasing requirement. For example, Reza Pour et al formulated a criterion for the selection of providers by the insurance organization and the ability to select a service provider and its payment mechanism, which are among the main terms of the contract as influencing components of the pragmatic model in purchasing expensive medical equipment (Rezapour et al, 2018). Dehnouyeh et al have identified the existence of a retrospective contractual mechanism between insurance organizations and health care providers as a major problem in the absence of strategic purchasing in Iran (Bastani et al, 2018;Dehnavieh et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The potential for a fair contract between the buyer and the service provider has been emphasized in many studies as a strategic purchasing requirement. For example, Reza Pour et al formulated a criterion for the selection of providers by the insurance organization and the ability to select a service provider and its payment mechanism, which are among the main terms of the contract as influencing components of the pragmatic model in purchasing expensive medical equipment (Rezapour et al, 2018). Dehnouyeh et al have identified the existence of a retrospective contractual mechanism between insurance organizations and health care providers as a major problem in the absence of strategic purchasing in Iran (Bastani et al, 2018;Dehnavieh et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Reviewing the related literature, it seems that strategic purchasing can bring many benefits to health care systems. For instance, according to Rezapour et al (2018), if national purchasers (the health insurance companies) are able to communicate with providers and to choose the best providers, receiving price information through competition in the most appropriate mechanism they can strategically buy the best and the most effective services for its insured population (Rezapour et al, 2018). Ogbuabor and Onwujekwe (2018) emphasized that some significant criteria such as strategic vision, participation and consensus, orientation, rule of law, transparency, responsiveness, equity and inclusiveness, effectiveness and efficiency, accountability and intelligence and information as well as ethics should be considered as governance framework principles to purchase strategically (Ogbuabor and Onwujekwe.…”
Section: Why National Upstream Documents Emphasize On Strategic Purchasing?mentioning
confidence: 99%
See 2 more Smart Citations